Microwave-induced activation of additional active edge sites on the MoS₂ surface for enhanced Hgᴼ capture - Zhao, Haitao; Mu, Xueliang; Yang, Gang; Zheng, Chengheng; Sun, Chenggong; Gao, Xiang; Wu, Tao (Elsevier, 2017)
In recent years, significant effort has been made in the development of novel materials for the removal of mercury from coal-derived flue gas. In this research, microwave irradiation was adopted to induce the creation of additional active sites on the MoS₂ surface. The results showed that Hgᴼcapture efficiency of the adsorbent containing MoS₂ nanosheets being microwave treated was as high as 97%, while the sample prepared via conventional method only showed an efficiency of 94% in its first 180 min testing. After the adsorbent was treated by microwave irradiation for 3 more times, its mercury removal efficiency was still noticeably higher than that of the sample prepared via conventional method. Characterization of surface structure of the MoS₂ containing material together with DFT study further revealed that the (001) basal planes of MoS₂ crystal structure were cracked into (100) edge planes (with an angle of approximately 75◦) under microwave treatment, which subsequently resulted in the formation of additional active edge sites on the MoS₂ surface and led to the improved performance on Hgᴼ capture.